Pengaruh Online Customer Review, Online Customer Rating, dan Service Quality terhadap Purchase Intention dengan Mediasi Trust pada Konsumen di E-commerce Shopee - Hermawan, Ilhan Hafizh; Astuti, Budi (Universitas Hamzanwadi, 2024)
This study aims to examine the impact of online customer review, online customer rating, and service quality on enhancing purchase intention among consumers on the Shopee e-commerce platform, with trust serving as a mediating variable. A quantitative approach was employed by distributing questionnaires to 160 Shopee users in Indonesia. Data analysis was conducted using PLS-SEM with the SmartPLS software version 4.1.0.4. The results indicate that customer reviews and ratings have a positive influence on purchase intention, whereas service quality shows no significant effect. Additionally, trust was found to be ineffective in mediating the relationships between customer reviews, ratings, and service quality with purchase intention